Residual Effect Of Ceftriaxone In Black Bengal Goats After Long Term Intramuscular Administration - BAKUL KUMAR DATTA; TAPAN KUMAR MANDAL; ANIMESH CHAKRABORTY (International Journal of Pharma and Bio Sciences, 2011)
Ceftriaxone was administered at 25 mg kg-1 daily by intramuscular injection for 60 days in goats. Blood, urine and feces samples were collected at every 7 days interval. Residual concentration of ceftriaxone and its metabolite ceftizoxime in blood, urine and feces showed a decreased pattern after 7 days onwards. Ceftriaxone and its metabolite (ceftizoxime) residue were recorded in kidney, lung, liver, spleen, adrenal gland and testis of goat sacrificed on day 60; while only metabolite (ceftizoxime) was identified in heart, fat, ovary, uterus, skin, bone, muscle and brain. Very low level of ceftriaxone and its metabolite (ceftizoxime) residue were detected in various tissues after withdrawal of ceftriaxone for 7 days.